2020
DOI: 10.21037/cco.2019.12.05
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose escalation for locally advanced unresectable intrahepatic and extrahepatic cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (IHCC) and extrahepatic cholangiocarcinoma (EHCC) remain challenging diseases to treat. The majority of patients present with advanced disease, and the tumors often cause life-threatening biliary obstruction and vascular compromise of the liver. Local control (LC) of these tumors has the potential to prolong life for patients. While escalated-dose radiation therapy (EDRT) has been demonstrated to be an effective, safe option to achieve LC of IHCC, data for EHCC suggest that EDRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Radiation dose escalation had been explored for improving the outcomes of several hepatobiliary cancers [ 16 , 17 , 18 , 19 ]. In the 20th century, Crane et al found that EBRT dose (30 Gy, 36–50.4 Gy and 54–85 Gy) is dose-dependent with median time to local progression (9 vs. 11 vs. 15 months), and no significant increase in toxicity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation dose escalation had been explored for improving the outcomes of several hepatobiliary cancers [ 16 , 17 , 18 , 19 ]. In the 20th century, Crane et al found that EBRT dose (30 Gy, 36–50.4 Gy and 54–85 Gy) is dose-dependent with median time to local progression (9 vs. 11 vs. 15 months), and no significant increase in toxicity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although local progression is a common cause of death in patients with unresectable BDC, distant metastasis is a still major pattern of failure in resected BDC [ 21 , 29 ]. In the present study, the patients experienced distant failure more frequently than local progression as the first site of failure.…”
Section: Discussionmentioning
confidence: 99%
“…RT has been regarded as an option for the treatment of locally advanced bile duct cancer [16][17][18][19][20]. For unresectable BDC, local progression is a major cause of cancer death and local control is important to improve the survival outcomes [19][20][21]. Several studies reported that the efficacy of RT for unresectable EHBDC in terms of 2-year OS ranged from 13% to 41%, and an analysis using the Surveillance, Epidemiology, and End Results (SEER)-Medicare database reported that RT with chemotherapy showed improved survival [16-18, 22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of dose escalation studies for the treatment of HC were not clearly as favorable as those for intrahepatic cholangiocacinoma[ 47 ]. A multi-center retrospective study of patients with HC reported improved median survival in patients receiving > 40.0 Gy compared with those receiving less.…”
Section: Radiotherapymentioning
confidence: 99%